To solve the equation 82.78(p + 11.892) = 72.8464 for p, let's begin by isolating p on one side of the equation.
82.78(p + 11.892) = 72.8464
First, distribute 82.78 to both terms inside the parentheses:
82.78p + 82.78(11.892) = 72.8464
The value of 82.78 multiplied by 11.892 is:
982.11296
Substituting the value above into the equation:
82.78p + 982.11296 = 72.8464
Next, subtract 982.11296 from both sides to isolate 82.78p:
82.78p = 72.8464 - 982.11296
Simplifying the right side of the equation:
82.78p = -909.26656
Finally, divide both sides by 82.78 to solve for p:
p = (-909.26656) / 82.78
p ≈ -10.97
So, when solving for p without rounding the answer, we get p ≈ -10.97.
what is the solution of 82.78 ( p + 11.892 ) = 72.8464 when solving for P do not round your answer
1 answer